The Effect of Stock Split on Price and Liquidity in Indian Stock Market - Alex, Dhanya; K.B, Pavithran (Ushus Journal of Business Management, 2021)
Stock splits are a relatively new phenomenon in the Indian context. This paper examines the market effect of stock splits on stock price, return, volatility, and trading volume around the split ex-dates for a sample of stock splits undertaken in the shares listed in NSE over the period 2000 to 2010.The traditional view of stock splits as cosmetic transactions that simply divide the same pie into more slices is inconsistent with the significant wealth effect associated with the announcement of a stock split.